SOCIALIZATION OF FINANCING SUPPORT IN AN EFFORT TO EMPOWER MICRO, SMALL AND MEDIUM ENTERPRISES (UMKM) - Rachmania; Emi Yulia Siska; Titin Hartini; Akbar Sarif (Bersama : Jurnal Pengabdian Masyarakat, 2023)
Empowerment of UMKMs in the face of intense competition and globalization UMKMs must be able to face global challenges such as expanding marketing horizons, creating innovative products and services, and investing in the development of technology and human resources.  This research uses a qualitative approach to the Socialization of Financing Support in Efforts to Empower Micro, Small and Medium Enterprises ("UMKM"). The location of this research was taken in Sidomulyo Village and was attended by all community members of Micro, Small and Medium Enterprises in Sidomulyo Village.  Naturally, high HR competence in a company or organization will determine the quality of HR owned and will ultimately determine business competitiveness. Similarly, HR competencies are very important for the growth of Micro, Small and Medium Enterprises ( UMKM).